Communication challenges in the hospitality business: Analysis of students' strategies in learning English at STIEPARI Semarang - Prabowo, Bayu Ade; Saptiany, Shella Gherina (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
This research aims to explore the communication challenges faced by students in the hospitality business and analyze English language learning strategies that can be used to address these challenges. The primary focus of this research is on students majoring in Hotel Accommodation at the School of Economics and Business (STIEPARI) Semarang. The main research questions involve understanding how communication challenges in the hospitality business affect students' English language communication abilities, what learning strategies can be employed by these students, and how effective these strategies are in improving their English speaking skills. The research methods include interviews, observations, and document analysis to obtain comprehensive data. The findings of this research are expected to provide in-depth insights into communication issues in the context of the hospitality business, offer recommendations for suitable English language learning strategies, and measure the effectiveness of their implementation. The findings from this research can contribute to a better understanding of how to enhance English communication skills among Hospitality major students, thus preparing them to tackle communication challenges that may arise in the hospitality industry in the future. This research is expected to serve as a basis for the development of more effective learning programs in this field.